Influence of dates of sowing on growth and yield of direct wet sown early ahu rice (Oryza sativa L.) varieties under flood prone lowland ecosystem of Asom - Satapathy, B.S.; Pun, K.B.; Singh, T.; Rautaray, S.K. (Annals of Agricultural Research, 2016)
A field experiment was carried out during early ahu (summer) season of 2013 and 2014 at the research farm of Regional Rainfed Lowland Rice Research Station, Gerua, Asom to study the influence of dates of sowing and varieties on growth and yield of direct wet sown rice during early ahu season in flood prone lowland ecosystem. The treatments consists of three dates of sowing viz., 5th Feb., 15th Feb. and 25th Feb. in main plots and two varieties viz., ‘Abhishek’ and ‘Naveen’ in sub-plots. Growth and yield attributes like days to 50% flowering, panicles per unit area, grains per panicle, test weight and grain filling percentage showed significant response to different dates of sowing. The crop sown on 15th February recorded higher grain yield of 5.41 t/ha. The high yield was due to more panicles per unit area, grains per panicle, test weight and grain filling %. Delay in sowing to 25th February resulted low grain and straw yield. This was due to poor grain filling % which in turn was due to high rain fall during flowering and grain filling stage. Among the two varieties tested, ‘Abhishek’matured early by 6 days and yielded (5.07 t/ha) compared to ‘Naveen’ (4.95t/ha). The later variety had more panicles per unit area (317.2 vs. 305.8) but less test weight of grains (20.5 vs. 22.2 g). Sowing of early ahu rice on 15th February recorded higher gross return and B:C ratio as compared to early or late sowing.